Analisis Frasa Pada Website Universitas Islam Riau - Pistalola, Ade Ria; S., Ermawati (UIR PRESS, 2021)
Phrases are part of the syntax which is formed from two or more words and their position in the clause is not more than one syntactic functionPhrases do not consist of subject-predicate structures, or predicate-object structures, but phrases consist of only subject, predicate, or object only. The problems described in this study are (1) What are the types of phrases found on the website of the Riau Islamic University? (2) What is the structure of the phrases on the website of the Riau Islamic University? The objectives of this study are. To analyze and describe the types of phrases and phrases structures found on the Islamic University Website. The theory that the writer uses to analyze this research is the theory put forward by Chaer (2009), Sulistyowati (2012), Miftahul and Sakura (2014). The method used is content analysis method. This type of research is library research (Library Research). The approach used is a qualitative approach. The data collection techniques used were documentation techniques and hermeneutic techniques. The data analysis techniques used were classification and interpretation. Based on the research carried out, it can be concluded that 1) the types of phrases found on the website of the Riau Islamic University are nominal phrases, verbal phrases, adjective phrases, prepositional phrases. So, the total nominal, verbal, adjective, and prepositional phrases found on the website of the Riau Islamic University are as many as 60 phrases. 2) the structure of the phrases found on the website of the Riau Islamic University, namely nominal phrases with as many noun + noun (N + N) structures and noun + adjective (N + A), verbal phrases with a verbal + noun (V + N) structure adjective (V + A), verbal + preposition (V + Prep), adverb + verbal (Adv + V) and verbal + verbal (V + V), adjective phrases with the structure of adjectivea + adverb (A + Adv), adjective + noun (A + N) and adverb + adjective (Adv + A), as well as prepositional phrases that have a prepositional + noun structure (Prep + N), prepositions + verbs (Prep + V) and prepositions + adjectives (Prep + A).